Proceedings of the 4th Sriwijaya University Learning and Education International Conference (SULE-IC 2020) 2020
DOI: 10.2991/assehr.k.201230.130
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners’ View on Online Learning Implementation During Covid-19 Outbreaks

Abstract: During the Covid-19 outbreaks, the teaching and learning practice in Indonesia has been implemented in online setting to prevent the spread of the disease, and study from home using digital technology as promoted in Education 4.0 became a burning issue. The mainly purpose of the study is to investigate the views of Indonesian undergraduate EFL learners in online learning implementation during the Covid-19 outbreaks. Data were collected through online interview, involving 6 participants and analysed by using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
1
12
2
Order By: Relevance
“…Sadeghi (2019) also illustrated that distant learning provides opportunities for students and workers willing to accomplish their learning process. The findings of this study differ from those of Melvina et al (2020), who stated that learners of English as a foreign language (EFL) faced many obstacles while learning online during the Covid-19 Pandemic, such as lack of knowledge and skills of online learning, as well as teachers' limited experience with online learning.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Sadeghi (2019) also illustrated that distant learning provides opportunities for students and workers willing to accomplish their learning process. The findings of this study differ from those of Melvina et al (2020), who stated that learners of English as a foreign language (EFL) faced many obstacles while learning online during the Covid-19 Pandemic, such as lack of knowledge and skills of online learning, as well as teachers' limited experience with online learning.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the result of the current study contradicts those of Melvina et al (2020), who stated that learners of English as a foreign language (EFL) faced many obstacles while learning online during the Covid-19 Pandemic, such as lack of knowledge and skills of online learning, as well as teachers' limited experience with online learning. Meanwhile, results showed that EFL students improve their language skills and English vocabulary, specifically in online learning through Microsoft Teams.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, many of the studies focused on using technology as a tool to enhance students' general English language ability via their online classes; the teachers usually controlled the lessons. When the teacher wants students to improve both their language skills, critical thinking, and problem-solving skills as well as content knowledge at the same time, a project-based learning approach integrated with the use of technology is usually recommended (e.g., Melvina et al, 2020;Yuliansyah & Ayu, 2021). Despite several previous studies focusing on online language learning in Thai contexts (e.g., Kanchai, 2021;Kawinkoonlasate, 2020;Sompakdee et al, 2021), there is a lack of research regarding the use of technology integrated with project-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have stated that the challenges of online learning in Indonesia are quite diverse. There are universities with lecturers who have limited experience with implementing applications for online learning (Melvina, Lengkanawati, Wirza, Alicia & Yulmiati, 2020). The cost of buying an Internet quota is quite expensive (Bahasoan, Ayuandiani, Mukhrom & Rahmat, 2020).…”
Section: Introductionmentioning
confidence: 99%